2011
DOI: 10.1089/pho.2009.2652
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Level Laser on the Speed of Orthodontic Movement

Abstract: The diode laser used within the protocol guidelines increased the speed of tooth movement. This might reduce orthodontic treatment time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(71 citation statements)
references
References 25 publications
4
67
0
Order By: Relevance
“…Furthermore, among the eight studies selected (RCTs and CCTs), six showed that LLLT could have a significant effect on orthodontic tooth movement [2,15,17,[21][22][23] (Table 4). …”
Section: Effect Of Lllt On Orthodontic Tooth Movementmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, among the eight studies selected (RCTs and CCTs), six showed that LLLT could have a significant effect on orthodontic tooth movement [2,15,17,[21][22][23] (Table 4). …”
Section: Effect Of Lllt On Orthodontic Tooth Movementmentioning
confidence: 99%
“…On day 60, the total tooth movement distance was 4.39 mm for the laser group and 3.0 mm for the control group, which represents a statistically significant difference [P < 0.001]. In the third study (by Sousa et al [22]), maxillary canine distalization was performed with a NiTi closed spring on a fixed appliance. After randomization, laser irradiation [780 nm] was applied on 10 points of the canine on days 0, 3, and 7.…”
Section: Effect Of Lllt On Orthodontic Tooth Movementmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of laser irradiation on orthodontic tooth movement has been attracting much attention over the past few years. Although it is indicated by numerous reports that tooth movement can be accelerated by diode laser irradiation, [7][8][9] there are only a few studies focused on other lasers. Ninomiya et al 10 revealed that neodymium-doped yttrium aluminium garnet (Nd:YAG) laser irradiation increased bone formation in femur metaphysis.…”
Section: Introductionmentioning
confidence: 99%